Effects of Three-Layer Encapsulated Tea Tree Oil on Growth Performance, Antioxidant Capacity, and Intestinal Microbiota of Weaned Pigs - Wang, Lixue; Zhang, Ying; Liu, Ling; Huang, Fei; Dong, Bing (Frontiers in Veterinary Science, 2021)
Tea tree oil (TTO) exerts key roles in improving growth performance of pigs. However, knowledge is limited regarding comparative effects of Encp TTO and Un-encp TTO supplementation on growth performance of pigs. A study determined the effects of TTO or its capsulation on growth performance, antioxidant capacity, and intestinal microbiome of weaned pigs. A total of 144 healthy pigs (8.5 ± 0.24 kg) were subjected to four treatments for a 28-d trial with six replicates per treatment and six pigs per pen: negative control, NC; positive control, PC (antibiotic supplemented); Un-encp TTO (supplemented with unencapsulated TTO); Encp TTO (supplemented with encapsulated TTO). NC, TTO, and PC treatments were compared with regard to improved average daily gain (ADG), average daily feed intake (ADFI), feed conversion rate, nutrient digestibility, and intestinal morphology (p < 0.05) and decreased diarrhea rate. TTO- and PC-treated pigs had higher levels of serum superoxide dismutase, glutathione peroxidase, and immunoglobulin G; lower levels of liver aspartate aminotransferase and alanine aminotransferase; and improved concentrations of interleukin 10 (IL-10), tumor necrosis factor α, and IL-1β (p < 0.05). TTO- and PC-treated pigs had higher abundance of beneficial bacterial species Subdoligranulum and lower abundance of diarrhea associated species Escherichia–Shigella in cecal and colonic digesta (p < 0.05). Encapsulation of TTO preserved more activities of TTO than its unencapsulated counterpart by showing higher ADG, ADFI, and feed conversion rate during day 1 (d1) to d14 (p < 0.05) and tended to lower diarrhea rate (p = 0.083) and improve villous height/crypt depth (VH/CD) ratio (p = 0.089) in jejunum. Encapsulation of TTO also improved antioxidant indexes and decreased liver injury and inflammation accordingly (p < 0.05). Encapsulated TTO-treated pigs had higher abundance of beneficial Clostridium_sensu_stricto_1 and lower the abundance of harmful Escherichia–Shigella in cecal and colonic digesta (p < 0.05). Our results demonstrated TTO benefits on improving growth performance of weaned pigs and further proved that encapsulation of TTO was superior to its unencapsulated counterpart at multiples. Encapsulated TTO was similar to the PC group and could be potentially an alternative of feed antibiotics for weaned pigs.